Ending the Search for Mr.Right - Mckinney, Hammond Michelle (Harvest House Publishers, 2005)
It's time we place our need for love in perspective, take our lives off hold, live purposely, and gain a better understanding of how to relate successfully to the opposite sex. The journey toward finding a mate for life doesn't have to be filled with anxiety, fret, or regret. The author will expertly navigate you through the choppy waters of singledom...
Keywords: Religious life; Mate selection; Non-Fiction; Single women